PRESTO: A Recommender of Musical Collaborations Based on Heterogeneous Graph Neural Networks - Terroso-Saenz, Fernando; Soto, Jesús; Muñoz, Andrés; Roose, Philippe (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
The music industry is now more complex and competitive than ever before. In recent years, the search for collaborations with other artists has become a common strategy for musicians to maintain their presence in the sector. Besides, existing music streaming services such as Spotify have exposed large data feeds that can be used to develop innovative services within the realm of music. In this context, the present work introduces PRESTO, a novel recommendation system to suggest musicians for new collaborations with other artists by means of an ensemble of Graph Neural Networks. The system is fed with a heterogeneous graph representing the time evolution and the stationary aspects of a musician’s career. Finally, the proposal has been evaluated with a dataset comprising more than 200,000 artists, with an average F1 score above 0.75.